Peran Guru Pendidikan Pancasila dan Kewarganegaraan dalam Meningkatkan Keberanian Siswa untuk Mengemukakan Pendapat (Lembaga Pengembangan Kinerja Dosen, 2026)
In the context of education, the courage to express opinions is an important indicator in shaping the character and skills of students. This courage reflects students' ability to convey ideas, thoughts, and arguments openly in front of teachers and classmates. This study aims to describe the role of teachers, the obstacles faced, and efforts to overcome these obstacles in increasing students' courage to express opinions, especially in Pancasila and Citizenship Education (PPKn) learning at SMK Negeri 1 Lolomatua. The research method used is qualitative with a descriptive approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Informants in this study consisted of six people, namely one PPKn subject teacher and five students who were selected purposively. The results of the study indicate that the role of teachers is very important in creating a classroom climate that is conducive to student courage. Teachers play a role in creating an open, democratic, and inclusive classroom atmosphere; use participatory learning methods such as group discussions; and serve as role models in expressing opinions politely. The main obstacles faced consist of internal factors such as lack of self-confidence, minimal understanding of the material, and limited communication skills. Meanwhile, external factors include an unsupportive learning environment and concerns about judgment or negative reactions from classmates. Teachers' efforts to overcome these obstacles include acknowledging every opinion expressed by students, conducting public speaking exercises or simulations, building a culture of mutual respect in the classroom, and communicating with parents to provide moral support at home. With a consistent approach, students' courage in expressing their opinions can be gradually and sustainably increased.